Hysterosalpingography with Oil-Soluble Contrast Medium Does Not Increase Newborn Hypothyroidism - Divya M. Mathews; Jane M. Peart; Neil P. Johnson; Robert G. Sim; Natasha L. Heather; Dianne Webster; Susannah O’Sullivan; Paul L. Hofman (International Journal of Endocrinology)
Objective. Hysterosalpingography (HSG) with oil-soluble contrast medium (OSCM) improves pregnancy rates in women with idiopathic infertility. However, OSCM has high iodine content and slow clearance resulting in potential iodine excess. If pregnancy occurs, this could impact fetal thyroid gland development and function. We aim to determine the effect of a preconceptional OSCM HSG on the thyroid function of the neonate. Design and Patients. This was a retrospective analysis of newborn TSH data for a cohort of neonates conceived within six months of an OSCM HSG in the Auckland region, New Zealand, from the years 2000 to 2019. Thyroid-stimulating hormone (TSH) levels of these newborns were obtained from newborn screening, which is routinely performed for all children at 48–72 hours of life. The primary outcome was the incidence of permanent or transient congenital hypothyroidism in this cohort. Results. Of 146 babies included, all had normal TSH levels with values ranging from 1 to 7 mIU/L on the whole blood analysis of a capillary heel sample using the Perkin–Elmer AutoDelfia assay. Conception during the first 3 cycles following an OSCM HSG was 76%; however, TSH levels in this group were not higher than those conceived in later cycles. Conclusion. Preconceptional OSCM HSG did not increase the risk of congenital hypothyroidism in the New Zealand scenario.